ANALISIS EFEKTIVITAS KREDIT PROGRAM SEKTOR PERTANIAN TERHADAP PENDAPATAN PETANI TEBU (Studi Kasus : Program Kredit Ketahanan Pangan dan Energi di Kabupaten Malang) - Priatna Saptayadi (TEMA, 2020)
The main objective of this study are (1) to determine the implementation of KKP-E that channeled by BRI for sugarcane farmers in Malang and (2) to determine the effectiveness of KKP-E by comparing the income of sugarcane farmers with KKP-E and without KKP-E in Malang. The samples are sugarcane farmers who are members of KUD Gondanglegi Malang. Samples are 100 people, consist of 50 sugarcane farmers with KKP-E dan 50 sugarcane farmers without KKP-E. The results of this study are: (1) the implementation of the KKP-E that channeled for sugarcane farmers in Malang already compliance with applicable regulations and farmers have felt the benefit of the KKP-E. But there are still some records related to administrative procedures, the time required from application until disbursement and the time of loan disbursement. (2) KKP-E is not effective in increasing the income of sugarcrane farmers, even though the income of sugarcane farmers with KKP-E is higher than income of sugarcane farmers without KKP-E. The increasing in income are more dependent on the yield of sugar cane, sugar price, cutting cost and transportation costs from the farm to the sugar mill. Moreover, KKP-E in this case is not the absolute variables in raising income.